A novel minimal motif for left-handed G-quadruplex formation. Issue 20 (8th February 2021) - Das, Poulomi; Winnerdy, Fernaldo Richtia; Maity, Arijit; Mechulam, Yves; Phan, Anh Tuân
Abstract : A novel minimal motif ( Motif2 ) for left-handed G-quadruplex (LHG4) formation has been discovered, highlighting the role of split guanines and single thymine loops in promoting LHG4 structures. Abstract : A recent study on the left-handed G-quadruplex (LHG4) DNA revealed a 12-nt minimal motif GTGGTGGTGGTG with the ability to independently form an LHG4 and to drive an adjacent sequence to LHG4 formation. Here we have identified a second LHG4-forming motif, GGTGGTGGTGTG, and determined the X-ray crystal structure of an LHG4 involving this motif. Our structural analysis indicated the role of split guanines and single thymine loops in promoting LHG4 formation.